Efficacy of single‐agent immunosuppressive regimens in a murine model of vascularized composite allotransplantation. (12th May 2020) - Guo, Yinan; Messner, Franka; Etra, Joanna W.; Beck, Sarah E.; Kalsi, Richa; Furtmüller, Georg J.; Schneeberger, Stefan; Chol Oh, Byoung; Brandacher, Gerald
Summary: We herein investigate the safety and efficacy of single‐agent anti‐rejection regimens in a mouse vascularized composite allotransplantation (VCA) model. Orthotopic hind‐limb transplantations (Balb/c → C57BL/6) were performed using 6‐ to 8‐week‐old mice. A thirty‐day regimen of either rapamycin, tacrolimus (both 1, 3, 5 mg/kg/day) or cyclosporine (25, 35, 50 mg/kg/day) was used. Primary endpoints were animal and graft survival, and secondary chimerism and regulatory T‐cell levels. For rapamycin and tacrolimus given at 1, 3, and 5 mg/kg/day, median graft survival time (MST) was 23 days (18–28 days), 30 days (23–30 days), and 30 d (30–30 days) and 14 days (13–18 days), 30 days (16–30 days), and 30 days (30–30 days), respectively. For cyclosporine dosed at 25 and 35 mg/kg/day, MST was 15 days (12–18 days) and 21 days (14–27 days). Toxicity from CsA 50 mg/kg led to 100% mortality. Mixed chimerism levels were higher in rapamycin‐treated animals than in tacrolimus‐treated recipients ( P  = 0.029). Tacrolimus was superior in preventing leukocyte recruitment to the allograft. In murine VCA, no standardized immunosuppressive regimen exists, limiting comparability of outcomes and survival. Our data demonstrate that rapamycin and tacrolimus maintenance treatment at 5 mg/kg/day both yielded allograft survival (<grade 3 rejection) in all animals. Rapamycin displayed less toxicity and maintained mixed chimerism but was not as potent in controlling leukocyte recruitment compared with tacrolimus.